Five-Year Risk of Stroke after TIA or Minor Ischemic Stroke - Pierre Amarenco; Philippa C. Lavallée; Linsay Monteiro Tavares; Julien Labreuche; Gregory W. Albers; Halim Abboud; Sabrina Anticoli; Heinrich J. Audebert; Natan M. Bornstein; Louis R. Caplan; Manuel Correia; Geoffrey A. Donnan; et al. (2018)
After a transient ischemic attack (TIA) or minor stroke, the long-term risk of stroke and other vascular events is not well known. In this follow-up to a report on 1-year outcomes from a registry of TIA clinics in 21 countries that enrolled 4789 patients with a TIA or minor ischemic stroke from 2009 through 2011, we examined the 5-year risk of stroke and vascular events.